Political Behavior of Novice Voters in the 2024 Presidential Election in Olimeyala Village, Biluhu District, Gorontalo Regency, Gorontalo Province - Cindi Pulango; Luciyane Djafar; Udin Hamdin (Universitas Muhammadiyah Palu, 2025)
his study aims to examine the political behavior of first-time voters regarding the 2024 Presidential Election in Olimeyala Village, Biluhu Sub-District, Gorontalo Regency. This study is motivated by the low level of political participation among first-time voters in the presidential election. The findings show that the political behavior of first-time voters in Olimeyala Village is influenced by several factors, such as a lack of understanding of democracy, limited political participation, and insufficient awareness of rights and obligations as citizens. This study is expected to contribute to efforts in increasing the political participation of first-time voters and to building awareness of the importance of democracy in society. This study examines the political behavior of first-time voters regarding the 2024 Presidential Election in Olimeyala Village. The findings also indicate that the level of participation among first-time voters is influenced by sociological, psychological, and rational choice factors. Sociological factors, such as social structure, norms, and social interaction, play a significant role in influencing access to political information and opportunities for participation. Psychological factors, including motivation, political awareness, personal experience, self-confidence, and understanding of rights and obligations, also determine their participation in the democratic process. Meanwhile, the rational choice approach shows that first-time voters in the village make political decisions logically based on the candidates' vision, mission, capabilities, and integrity. The inhibiting factors of political awareness among first-time voters include limited political education, lack of effective socialization, and political apathy. Therefore, it is expected that a more democratic, just, prosperous, and stable society can be fostered in Olimeyala Village. Furthermore, this study contributes to the theory of political behavior and democratic participation and provides recommendations for election organizers and the government to improve the quality of democracy in Indonesia.